Propuesta para el desarrollo de un carbón activado magnético partiendo del elote de maíz (tusa) (2021)
The main objective of this research project is to make a proposal for the development of a magnetic activated carbon starting from the corn cob. In this way, a bibliographic review of activated carbon is carried out, where its characteristics, the adsorption process for the elimination of pollutants and the factors that can affect it, the methods of operation and obtaining of activated carbon, as well as its industrial applications and how to make the selection of a good adsorbent. After studying the conditions that a good adsorbent must meet, it was decided to take corn cob as a precursor, so the opportunities in Colombia were studied using this as a raw material for the development of a magnetic activated carbon. . Once all the information from the literature has been compiled, the conditions and parameters for the synthesis of activated carbon are identified starting from the corn cob to later establish a methodology for the synthesis of magnetic activated carbon and thus be able to identify and characterize the applications. of this adsorbent. Additionally, it was decided to carry out a cost analysis for the production of magnetic activated carbon at the pilot plant level in order to identify the necessary resources to carry out this project.